2019
DOI: 10.1111/ecno.12140
|View full text |Cite
|
Sign up to set email alerts
|

The impact of foreign and domestic remittance types and senders on education outcomes

Abstract: Migration and remittances are very important for Nepal, yet the country continues to be plagued by low financial development. Increases in human capital investments, such as enrollment of school‐aged children, are a possible gain from the country's labor movements, which can be leveraged further through an understanding of the microeconomic processes involved. This study examines how remittances from both household and nonhousehold members affect school enrollment rates for children in Nepalese families. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…The impact of remittances on the enrolment rates of children in Nepalese families was studied, considering whether the remittance sender was a household or non-household member, as well as their type and location. The study found that there were both positive and negative effects of remittances on education outcomes Stanley & Fleming, 2019). Thus, all the interpretations of the tables and charts mentioned above behaves as an answer in the sense of the positive confirmation to the notion that in general the usage of type of remittance have a preferred order as displayed in table 9.…”
Section: Types Of Remittance Usagementioning
confidence: 66%
See 1 more Smart Citation
“…The impact of remittances on the enrolment rates of children in Nepalese families was studied, considering whether the remittance sender was a household or non-household member, as well as their type and location. The study found that there were both positive and negative effects of remittances on education outcomes Stanley & Fleming, 2019). Thus, all the interpretations of the tables and charts mentioned above behaves as an answer in the sense of the positive confirmation to the notion that in general the usage of type of remittance have a preferred order as displayed in table 9.…”
Section: Types Of Remittance Usagementioning
confidence: 66%
“…It is important to note that the impact of remittances can vary depending on various factors such as the source of remittances, the type of remittance sender, and the volatility of remittance inflows Stanley & Fleming, 2019). The impact of remittances on the enrolment rates of children in Nepalese families was studied, considering whether the remittance sender was a household or non-household member, as well as their type and location.…”
Section: Types Of Remittance Usagementioning
confidence: 99%